Dysregulated genes and their functional pathways in luteinized granulosa cells from PCOS patients after cabergoline treatment. Issue 4 (April 2018) - Ferrero, H; Díaz-Gimeno, P; Sebastián-León, P; Faus, A; Gómez, R; Pellicer, A
Abstract : Polycystic ovarian syndrome (PCOS) is a common reproductive disorder frequently associated with a substantial risk factor for ovarian hyperstimulation syndrome (OHSS). Dopamine receptor 2 (D2) agonists, like cabergoline (Cb2), have been used to reduce the OHSS risk. However, lutein granulosa cells (LGCs) from PCOS patients treated with Cb2 still show a deregulated dopaminergic tone (decreased D2 expression and low dopamine production) and increased vascularization compared to non-PCOS LGCs. Therefore, to understand the PCOS ovarian physiology, it is important to explore the mechanisms that underlie syndrome based on the therapeutic effects of Cb2. Here, LGCs from non-PCOS and PCOS patients were cultured with hCG in the absence/presence of Cb2 ( n = 12). Subsequently, a transcriptomic-paired design that compared untreated vs treated LGCs within each patient was performed. After transcriptomic analysis, functions and genes were prioritized by systems biology approaches and validated by RT-qPCR. We identified that similar functions were altered in both PCOS and non-PCOS LGCs treated with Cb2; however, PCOS-treated LGCs exhibited more significant changes than non-PCOS. Among the prioritized functions, dopaminergic synapse, vascular endothelial growth factor (VEGF) signaling, apoptosis and ovarian steroidogenesis were highlighted. Finally, network modeling showed CASP9, VEGFA, AKT1, CREB, AIF, MAOA, MAPK14 and BMAL1 as key genes implicated in these pathways in Cb2 response, which might be potential biomarkers for further studies in PCOS.